Analysis of tobacco and cannabis smoke and its toxicological impact in neuroblastoma tumour cells - Grafinger, Katharina (My University, 2015)
The dried products of Cannabis sativa have been consumed for their psychoactive effects for thousands of years. Almost five hundred different natural cannabinoids could be identified in Cannabis sativa with Δ9-THC being the most psychoactive one. The most effective way of consumption is by smoking, because it avoids digestion and the first pass in the liver. Usually so called "joints" are rolled in a 1:1 ratio of dried cannabis and tobacco filler. The reason for this is that cannabis has a lower burning efficiency and that tobacco is cheaper. Processed Nicotina tabaccum contains about 0.6- 9 % nicotine; an oily, volatile liquid alkaloid. Pyrolysis of tobacco and cannabis leads to the formation of new products whose cytotoxicity is not yet established. This study investigates the effect of smoke of tobacco, cannabis and their mixture in similar conditions as humans uptake it. For production of smoke an in-house developed smoking device was used which trapped the water-soluble and organic-soluble molecules separately. Qualitative analysis of the smoke was performed using GC-MS and measurement of cytotoxicity on neuroblastoma tumour cells SH-SY5Y was performed using the MTT assay. SH-SY5Y cell line selectively expresses Cannabinoid 1 (CB1) receptor and Nicotinic acetylcholine receptor (nAChR). The results allow us to identify several pyrolysated products which are hydroxylated forms of nicotine and Δ9-THC. Moreover, MTT analysis strongly suggests different toxicological impact between smoke of tobacco, cannabis and their mixture. In fact our results points smoke from the mixture of tobacco and cannabis having the higher impact on cell viability followed by the smoke of tobacco which in turn is more toxic than smoke of cannabis, the least toxic compound out of these three. This study shows that at 100 μM cannabis has a cell viability of 80 % while tobacco and the mixture have around 40 %.
Dissertação de Erasmus Mundus para obtenção do grau de mestre em Técnicas Laboratoriais Forenses
Keywords: GC-MS; Pyrolysis; Cannabis; Tobacco; Cytotoxicity